Perceptions of People with Disabilities on the Accessibility of New Zealand’s Built Environment - Flemmer C; McIntosh A (MDPI (Basel, Switzerland), 2025)
Accessing the built environment poses many challenges for people with disabilities, severely affecting their independence and quality of life. A panel of experts with a lived experience of disabilities co-designed a survey capturing the challenges in New Zealand’s public places. There were 319 survey respondents with impairments related to mobility (66.5%), vision (18.8%), hearing (5.0%), sensory processing and cognition (8.8%). They perceived sports stadiums as the least accessible venue, followed by bars, boutique shops and public toilets. The most accessible venues were supermarkets, libraries and shopping malls. The type of disability affected the main accessibility challenges. Significant outdoor barriers included uneven and cluttered paths, inadequate provision of curb cuts, seating and accessible parking spaces, and obscure wayfinding. Entrance barriers included heavy doors, complex access control, remote ramps and narrow, obscure entrances. Interior problems included cluttered paths and poor signage. The top priorities for improvement were simplifying layouts, keeping paths clear, and providing clear, inclusive signage, communication and assistance for people with varying impairments. Providing lower counters, better colour contrast, hearing loop facilities and better control of lighting and acoustics also improve accessibility. This research contributes novel experiential data from people with disabilities that is critical to achieving an inclusive built environment.
Keywords: accessibility; built environment; disability